1991
DOI: 10.1007/bf02260432
|View full text |Cite
|
Sign up to set email alerts
|

Size distribution of dissolved (<200 nm) organic carbon and aluminium in alkaline and humic lakes

Abstract: Chemical equilibrium calculations treating humic substances as the simple diprotic phtalic acid, predicted no AI-humus at pH >6.5 in humic lake water. However, dissolved (<200 nm) organic carbon (DOC) and dissolved AI appeared to be linearly (r = 0.597, P <0.001) correlated in samples from five different humic surface waters in The Netherlands with a DOC range of 10-36 mg.1-1 and a (mean) pH range of 6.85-8.47. Yet, organic carbon (Corg) and AI did no exhibit similar size distributions between 5 and 200 nm rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…showed phosphate adsorption onto Al(OH) 3 in experiments in vitro, where high concentrations of Al(OH) 3 were used in limited volumes. De Haan et al (1991) found concentrations of soluble (< 200 nm) Al between 10 and 50 µg −1 in 5 humic rich Dutch lakes with pH values between 6.85 and 8.5 and suggested a linear correlation with org-C diss . These data are more relevant for P-elimination from sewage water than from lakes and cannot be used in a lake situation.…”
Section: Syers and Curtinmentioning
confidence: 96%
“…showed phosphate adsorption onto Al(OH) 3 in experiments in vitro, where high concentrations of Al(OH) 3 were used in limited volumes. De Haan et al (1991) found concentrations of soluble (< 200 nm) Al between 10 and 50 µg −1 in 5 humic rich Dutch lakes with pH values between 6.85 and 8.5 and suggested a linear correlation with org-C diss . These data are more relevant for P-elimination from sewage water than from lakes and cannot be used in a lake situation.…”
Section: Syers and Curtinmentioning
confidence: 96%